Convergent innovation for affordable nutrition, health, and health care: The global pulse roadmap - Jha, Srivardhini K.; McDermott, John; Bacon, Gordon; Lannon, Chris; Joshi, Pramod Kumar; Dubé, Laurette (Wiley, 2014)
The paper outlines how the principles of convergent innovation (CI) can be applied to bring about a transformation in the pulse value chain. The paper presents three pioneering CI initiatives––two in conception and one in operation––by various actors in the pulse ecosystem, which are delivering economic and human development impact in particular segments of the pulse value chain. It goes on to propose the way forward to scale up these efforts and connect them into a roadmap so as to achieve transformation throughout society, calling into action a number of actors in the ecosystem.